The Method of Identification and Analysis of the Possibility of Forming a Regional Tourist Cluster: an Example from the Republic of Uzbekistan - Aslanova Dilbar Hasanovna (Indonesian Journal of Law and Economics Review, 2019)
In the article, having studied the socio-economic importance of tourism development, the proposal to form regional tourist clusters in the regions of the Republic of Uzbekistan is scientifically substantiated. The main approaches to the definition of the concept of "tourist cluster", methods for identifying clusters are considered. A methodical approach is proposed, using an integral localization coefficient to identify the process of forming a regional tourist cluster.